Prenatal diagnosis of trisomy 11 in a single colony of cultured amniocytes at amniocentesis in a pregnancy with a favorable outcome - Chih-Ping Chen; Cheng-En Hsieh; Schu-Rern Chern; Shin-Wen Chen; Fang-Tzu Wu; Dai-Dyi Town; Wayseen Wang (Elsevier, 2021)
Objective: We present prenatal diagnosis of trisomy 11 in a single colony of cultured amniocytes at amniocentesis and the perinatal outcome. Case report: A 36-year-old, gravida 2, para 1, woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XX,+11[1]/46,XX[16]. In 17 colonies of cultured amniocytes, all five cells in one colony had a karyotype of 47,XX,+11, while the rest 16 colonies had a normal karyotype. The parental karyotypes were normal. Repeat amniocentesis was performed at 21 weeks of gestation. Interphase fluorescence in situ hybridization (FISH) was applied on the uncultured amniocytes, and the result revealed 0.9% mosaicism (1/101 cells) for trisomy 11 with only one cell with three signals, while the other 100 cells had two signals, compared with no trisomy 11 signals (0/100 cells) in the normal control. Uniparental disomy (UPD) 11 was excluded by polymorphic DNA marker analysis on the DNAs extracted from uncultured amniocytes and parental bloods. The cultured amniocytes at repeat amniocentesis revealed a karyotype of 46, XX in 28/28 colonies. Prenatal ultrasound findings were unremarkable. The pregnancy was continued to 38 weeks of gestation, and a 2724-g healthy female baby was delivered. The cord blood had a karyotype of 46,XX. The interphase FISH analysis on buccal mucosal cells revealed no trisomy 11 signals (0/100 cells). When follow-up at three months of age, the neonate manifested normal psychomotor and physical development. Conclusion: Prenatal diagnosis of mosaic trisomy 11 in a single colony at amniocentesis without abnormal fetal ultrasound and UPD 11 can be associated with a favorable outcome.